Factors influencing preferences of Korean people toward advance directives - Kim, Su Hyun (Nursing ethics, 2011)
Although Korean society has begun to seek a way of utilizing advance directives, there is not much known about the factors influencing the average Korean person’s preference toward advance directives. The purpose of this study was to examine factors, in addition to demographic variables, influencing preferences regarding advance directives. These include: to what extent people’s awareness of advance directives, preferences of extending their life at the end of life, experience of illness and medical care, and family functioning independently influence the preferences toward advance directives. The participants were 382 community-dwelling Korean people. The data analysis was performed using hierarchical multiple logistic regression analysis. The findings showed that a majority of Korean people had a positive preference on advance directives and the factors influencing their preferences for advance directives were the preferences against the use of life-sustaining treatment at the end of life, a good self-rated heath status, and an unsatisfactory family functioning.